2006
DOI: 10.1111/j.1745-4603.2006.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Allo–kramer, Warner–bratzler and Razor Blade Shears for Predicting Sensory Tenderness of Broiler Breast Meat

Abstract: Regression models were established to predict sensory tenderness of broiler pectoralis major muscles from instrumental shear values. Birds were processed and the breasts were removed at one of nine postmortem (PM) deboning times: 0.25, 1.25, 2.0, 2.5, 3.0, 3.5, 4.0, 6.0 and 24.0 h. A seven‐member trained panel evaluated the cooked samples for initial hardness, cohesiveness, moisture release, hardness of mass, cohesiveness of mass and number of chews. A 74‐member consumer panel was used to evaluate the samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 20 publications
1
68
7
1
Order By: Relevance
“…No difference between 24 h sample and the hot-boned sample for cohesiveness could be due to the different responses of the hot-boned muscle versus the chilled meat to freezing temperature. Yu et al (2005) found that thawing the frozen, hot-boned chicken leg muscle resulted in significantly reduced shear force values of cooked samples. Xiong et al (2006) reported that the intensity score for cohesiveness of hot-boned broiler fillets was more than 1.5 units lower than that of 2-h deboned fillets.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…No difference between 24 h sample and the hot-boned sample for cohesiveness could be due to the different responses of the hot-boned muscle versus the chilled meat to freezing temperature. Yu et al (2005) found that thawing the frozen, hot-boned chicken leg muscle resulted in significantly reduced shear force values of cooked samples. Xiong et al (2006) reported that the intensity score for cohesiveness of hot-boned broiler fillets was more than 1.5 units lower than that of 2-h deboned fillets.…”
Section: Resultsmentioning
confidence: 97%
“…Hot-boning and earlier cold-deboning (<4 h PM) resulted in unacceptable meat toughness (Lyon and Lyon, 1990b;Xiong et al, 2006), and PM cold-deboning time resulted in flavor changes (Liu, Lyon, Windham, Lyon, & Savage, 2004). In duck PM deboning time had significant effects on tenderness and flavor of both breast and thigh meat.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…TPA is one of the methods that simulate the conditions to which the food is exposed in the mouth [34]. The textural property changes, including those pertaining to the hardness, adhesiveness, chewiness, rigidity, cohesiveness, springiness, and elasticity of the cooked and uncooked zebra blenny fillets are shown in Table 5.…”
Section: Textural Properties Of Zebra Blenny Filletsmentioning
confidence: 99%